2018
DOI: 10.1002/ccr3.1789
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of a spiradenoma with blaschkoïd pattern

Abstract: Key Clinical MessageEccrine spiradenoma is a benign and rare adnexal tumor originating from cutaneous eccrine sweat glands. It usually presents as a solitary lesion. It can have different presentations, including a blaschkoid arrangement which is rare. Malignant transformation is possible and usually occurs after a long period of latency in multifocal types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Moreover, several studies have reported multiple nodules (11) or a linear zosteriform pattern (12)(13)(14). The typical clinical manifestation of MES is malignant transformation from a long-standing benign ES lesion with recent rapid growth, color change, erythema, ulceration, new-onset pain and bleeding (1,(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have reported multiple nodules (11) or a linear zosteriform pattern (12)(13)(14). The typical clinical manifestation of MES is malignant transformation from a long-standing benign ES lesion with recent rapid growth, color change, erythema, ulceration, new-onset pain and bleeding (1,(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…ES is an uncommon, benign adnexal tumor characterized by one or more nodules. The tumor has been described as " blue ball in the dermis " because of its blue color, although it might be purple, red, pink or gray [3]. Few clinical variants have been described like solitary ES which is generally accepted as the most common, multiple ES and giant vascular ES.…”
Section: Discussionmentioning
confidence: 99%
“…Spiradenomas are well-differentiated, benign, and dermal neoplasms that arise from the hair follicle bulge rather than the eccrine sweat gland, based on an immunohistochemical study of stem cell markers and with CD200 [ 248 ]. The pathogenesis is not entirely understood, but a defect in the tumor suppressor gene, CYLD , is thought to contribute to their development in Brooke-Spiegler syndrome, which also features multiple spiradenomas [ 249 ].…”
Section: Tumors With Apocrine and Eccrine Differentiationmentioning
confidence: 99%